Penerapan Aplikasi Monopoly Dental (Molydent) Game sebagai Media Edukasi Kesehatan Gigi dan Mulut pada Siswa Sekolah Dasar - Amran, Ricky; Ferdina, Resa; Ningrum, Princess R. S. (Universitas Sam Ratulangi, 2026)
Abstract: Person's awareness of the importance of dental health can be seen from his/her knowledge. To improve a person's dental and oral health, various media can be used; one of which is the Monopoly Dental (Molydent) game. Molydent is a monopoly game that contains learning materials about dental and oral health. This study aimed to analyze the effect of using the Molydent application as an educational medium on the knowledge of elementary school students with a one-group pre-test post-test design on 27 respondents. The results obtained 27 students of grade 3B at SDN 10 Sungai Sapih Kota Padang as respondents. Male students were predominant than female students (55.56% vs 44.44%). The most frequent age was nine years (63%). The mean score before intervention of molydent game was 8.30, and after intervention was 9.59, with a maximum score of 10. The Wilcoxon signed ranks showed that there was a significant influence of education using the molydent game on the students’ knowledge about dental and oral health with a p-value of 0.000 (p<0,05). In conclusion, Molydent game is effective in improving the knowledge of dental and oral health among elementary school students. Keywords: Molydent game; education media; interactive application Abstrak: Kesadaran seseorang akan pentingnya kesehatan gigi dapat dilihat dari pengetahuan yang dimilikinya. Untuk meningkatkan kesehatan gigi dan mulut seseorang, dapat dilakukan dengan berbagai media, salah satunya media monopoly dental (molydent) game. Molydent adalah permainan monopoly yang mengandung materi pembelajaran mengenai kesehatan gigi dan mulut. Penelitian ini bertujuan menganalisis pengaruh penggunaan aplikasi Molydent sebagai media edukasi terhadap pengetahuan siswa sekolah dasar dengan desain one group pre-test post-test pada 27 responden. Hasil penelitian mendapatkan 27 siswa kelas 3B SDN 10 Sungai Sapih Kota Padang sebagai responden penelitian. Jenis kelamin laki-laki (55,56%) lebih banyak daripada perempuan (44,44%), dengan usia terbanyak ialah usia 9 tahun (63%). Nilai rerata sebelum intervensi menggunakan aplikasi molydent game ialah 8,30 dan setelah intervensi ialah 9,59 dengan nilai maksimumnya ialah 10. Hasil uji Wilcoxon signed ranks menunjukkan bahwa terdapat pengaruh edukasi kesehatan gigi dan mulut menggunakan media Molydent game terhadap pengetahuan kesehatan gigi dan mulut siswa SDN 10 Sungai Sapih Kota Padang dengan nilai p=0,000 (p<0,05). Simpulan penelitian ini ialah aplikasi Molydent game berpengaruh terhadap peningkatan pengetahuan kesehatan gigi dan mulut siswa sekolah dasar. Kata kunci: Molydent; media edukasi; aplikasi interaktif